Discovery of Structural Elements that Form Amorphous Materials - Kucherov, Olexandr; D. Rud, Alexandr (New Environmentally-Friendly Materials, 2025)
One of the important and unresolved problems of materials science is the structure of amorphous solids. This paper reveals the secret of the structure of amorphous materials through picoscopic visualization of electron orbitals. Picoscopy is a precision experimental method for measuring the thickness of a real electron orbital body in the metric unit picometers. The results of the study of thousands of electron orbitals in amorphous carbon revealed the absence of crystal-forming elements: a) short-range order and b) strong covalent chemical bonds. However, it was found that atoms in amorphous solids are bound by unpaired valence electrons, which form weak interactions due to dipole polarization. Therefore, chemical bonds in amorphous solids are different from those in crystals. Accordingly, the amorphous solids are allotropes. This study shows that unpaired electron interactions form previously unknown polygons with the general formula Cn: a) triangle (C3); b) quadrangle (C4); c) pentagon (C5); d) hexagon (C6). The polygons create the short-range structure of the amorphous solids. It is polygons that are responsible for the universal spatial parameter of the order of ~300 pm, with which the structure of amorphous solids of various natures (semiconductor, dielectric, and metallic) is associated. The unpaired electron interaction and polygons play a fundamental role in the nature of amorphous materials.